Alleviation of Adverse Effects of Sodium on Soil Physicochemical Properties by Application of Vermicompost. Issue 2 (2nd April 2020) - Demir, Zeynep
Abstract: The objective of this study was to examine the influence of vermicompost (VC) as a soil conditioner in alleviating adverse effects of sodium in Na salt-effected soils. Therefore, the role of VC for reducing the adverse effects of Na salt on physicochemical properties of soil was investigated. Experiments were conducted with different doses of VC (0, 2.5 and 5% VC (w/w) and three different Na salt levels (0, 4 and 8 dS m −1 NaCl). Vermicompost treatments under different salinity stress levels had significant positive effects on soil physicochemical properties. Vermicompost also decreased exchangeable Na of salt-affected soils. Vermicompost treatments under different Na salt regimes enhanced soil organic matter, available phosphorus, total nitrogen, available K and cation exchange capacity of the soils. VC treatments under the low and medium Na salt levels (0 and 4 dS m −1 NaCl concentration, respectively) increased soil EC values. However, vermicompost treatments under high Na salt stress (8 dS m −1 NaCl concentration) decreased EC values, thus soil salinity. Vermicompost treatments under different Na salt regimes increased field capacity, available water capacity, saturated hydraulic conductivity, total porosity, aggregate stability and decreased bulk density of the soils. Present findings revealed that vermicompost treatments, especially 5% VC treatments were quite effecient in alleviating adverse effects of salinity and enhancing soil quality. It was concluded based on present findings that vermicompost treatments could be considered as an efficient amelioration material for reclamation of Na salt-effected soils.